ANALISIS SURVIVAL PASIEN RAWAT INAP DIABETES MELITUS TIPE-II MENGGUNAKAN METODE KAPLAN MEIER DI RSUD KUALA PEMBUANG - Ananda, Rosa; Salam, Nur; Noor, Meitria Syahadatina (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN (EPSILON: JOURNAL OF PURE AND APPLIED MATHEMATICS), 2024)
Diabetes mellitus (DM) is a chronic metabolic condition characterized by high blood sugar levels caused by insulin deficiency. According to data from the International Diabetes Federation, as many as 80% of diabetes patients worldwide live in developing countries, one of which is Indonesia. Indonesia ranks fifth in the world for the highest number of diabetes patients, including the Kuala Pembuang area with a rate of 1.1%. This study aims to determine whether there are differences in each variable affecting the length of hospitalization for patients with type-II diabetes mellitus at RSUD Kuala Pembuang, and to determine this, survival analysis methods such as the Kaplan-Meier method and Log Rank Test were used. Secondary data from the medical records of RSUD Kuala Pembuang were utilized. The data used during the research over the period of 2020 included age, gender, blood glucose levels, comorbidities, and blood pressure. The result of this study is that female patients over the age of 45 are more numerous than male patients. Patients with comorbidities have blood pressure of 140/90 mmHg or higher, as well as inpatient blood glucose levels of 200 mg/dL or higher. Log Rank test analysis shows a significant gap between age groups and comorbidities.